The very fairy princess - Here comes the flower girl! - Andrews, Julie 1935-; Hamilton, Emma Walton 1962- (Little, Brown and Company, 2012)
When disaster strikes in the form of rain on Aunt Sue's wedding day, flower girl and self-proclaimed fairy princess Geraldine finds a way to bring sunshine to the party, reminding everyone that the most important thing at a wedding is the most special sparkle of all--happiness and love.
Keywords: Flower girls -- Fiction; Weddings -- Fiction; Princesses -- Fiction; Hochzeit; Bilderbuch